LEARNING MODEL BASED ON PANDE TRADITIONAL GAME TO STRENGTHEN STUDENT CHARACTERS - Yuniatun Dwi Nurriskah; Idzza Zubdatun Thoyyibah; Muhamad Chamdani (Universitas Sebelas Maret, 2018)
This article aims to create new innovations on learning models so that learning in elementary schools can take place effectively and be able to strengthen student character development. The research method used is literature study. Data collection is carried out with studies of books, literature, records, and reports relating to the problem being solved. Literature sources in this study were obtained from books, journals, and research results. This research includes the process of systematically identifying the theory, finding literature, and analyzing documents that contain information related to the research topic. The results of this study are in the form of learning models that can be applied by the teacher to achieve the learning objectives effectively and strengthen student character development.